Comparison of the Influence of Polypropylene (PP) or Polybutylene Terephthalate (PBT)-Based Meltblown and Polyester/Polyamide-Based Hydroentangled Inner Layers on the Sound and Thermal Insulation Properties of Layered Nonwoven Composite Structures - Cincik, Emel; Kocatepe, Sureyya; Aslan, Eda (Mdpi, 2025)
Thermal and sound insulation play a vital role in today's world, and nonwoven composite structures including microfiber layers provide efficient solutions for addressing these demands. In this study, the sound and thermal insulation properties of nonwoven composite structures, including single-layer meltblown, multilayer meltblown, hydroentangled, and nanofiber nonwoven inner layers, were compared statistically by using Design Expert 13 software. The inner layer type and outer layer type of the composite structures were considered as independent variables, and thickness, bulk density, air permeability, sound absorption coefficient, and thermal resistance of composite structures were evaluated as dependent variables during statistical analyses. The effects of layer types on dependent variables were investigated comparatively, and the best inner and outer layers for high sound and thermal insulation were determined. It was concluded that the developed nonwoven composites including hydroentangled and three-layered meltblown layers demonstrated superior sound absorption properties at low (changing between 48% and 70%) and moderate (ranging between 77% and 96%) sound frequencies, respectively, when compared to composites and materials including single-layer meltblown or nanofiber nonwoven structures reported in prior studies. Additionally, it can be inferred that the composite structures obtained in this study exhibited thermal resistance properties (0.49 to 0.73 m2K/W) comparable to those of commercial thermal insulation materials.
Keywords: sound insulation; heat insulation; meltblown nonwovens; hydroentangled nonwovens